Replication Data for: Bean experimental lines selected for tolerance to Drought, high temperatures, low P in the soil, high aluminum in the soil and high content of Fe / Zn in grain - Raatz, Bodo; Beebe, Stephen E. (International Center for Tropical Agriculture, 2020)
Bean experimental lines selected for tolerance to Drought, high temperatures, low P in the soil, high aluminum in the soil and high content of Fe / Zn in grain. These lines will be sent to collaborators in Central America and Africa to be evaluated under their local conditions. Yield in Kg / Ha and Fe / Zn content in mg / Kg were evaluated.